Simultaneous measurement of particle charge, distance and size using coaxial induction probe - M Murtomaa; J Salonen (United Kingdom, 2026)
A novel probe for charge measurements was simulated, designed and tested. It consisted of two coaxial induction probes which were grounded via a current sensing circuit. As a charged spherical object passed the probe, data was collected and analyzed using a PC running a program compiled with LabVIEW. Two simultaneous current signals were integrated to obtain induced charges as a function of time. Then, Gaussian curves were fitted to the data and widths and amplitudes were collected for further processing. According to simulations performed with Comsol MultiPhysics, object charge, distance from the probe and size could be calculated using the above mentioned Gaussian peak parameters. The probe was calibrated and tested using induction charged water droplets and frictionally charged insulating spheres.